Parametric investigation on the responses of laterally loaded piles in overconsolidated clay using nondimensional solutions addressing nonlinear soil-pile interaction. (April 2018) - Su, D.; Huang, J.J.; Yan, W.M.
Abstract: This paper presents nondimensional solutions and parametric studies of the responses of laterally loaded piles in overconsolidated clay. Nondimensional expressions of a nonlinear p - y model, termed as the H-model, and the governing equation of laterally loaded piles were derived and solved. Parametric studies by virtue of the nondimensional solutions were conducted, which revealed that the pile head response is highly sensitive to the change in the soil undrained shear strength ( s u ), the maximum lateral bearing factor ( n p(max) ), and the ratio of the elastic modulus of subgrade reaction to the soil undrained shear strength ( n k ), but is insensitive to other parameters in the model.